(untitled) (Journal of Economic Research & Business Administration, 2015)
The article examines the role of the housing market in the country’s economy, that is, it shows the role in the socioeconomic development. Reveals the essence of the concept of housing specified in the law. Analyzes the key stages and modern trends in the real estate market of the Republic of Kazakhstan. Described the years of the birth of the construction industry in Kazakhstan and its development. Housing development described in three stages through a change in the number of construction organizations, the volume of investment in construction industry and the dynamics of prices shows the positive and negative trends in residential construction caused by the financial crisis. There are analyzed the factors which affecting the housing construction and housing prices. Programs of housing policy are considered, revealed their flaws.